Pengaruh Kepemimpinan, Budaya Organisasi dan Lingkungan Kerja terhadap Kepuasan Kerja Pegawai Kantor Camat Siulak Kabupaten Kerinci - Mauledy Ahmad (Syntax Corporation, 2023)
This study aims to determine and analyze how the influence of Influence of leadership,Organizational Culture and Work Environment Job Satisfaction of Siulak sub district office employees Kerinci district. This research is categorized as a causal comparative quantitative approach with an instrument in the form of a questionnaire. The population in this study were all civil servants except the head of the Social Service, Kerinci Regency as many as 21 people. The sampling technique is by means of a saturated sampling technique or a census. The sample in this study is to take the population or as many as 21 samples. The data used in this study are primary data obtained through questionnaires and secondary data obtained from related agencies and journals to support this research. The instrument validity test used the Bivariate Correclation formula, while the reliability test used Cronbach Alpha. The measuring instrument proved to be valid and reliable for the research instrument. Multiple regression analysis was used to test the hypothesis of this study. The results showed that: Leadership(X1) no influence significant effect on job satisfaction at the sub district office employees, Kerinci district of (Î²) 1,105 with a significance of 0.132. Organizational Culture(X2) has negatife and no significant effect on job satisfaction at the sub district office employees, Kerinci district, as evidenced by the value (Î²) of -1,201. Work Evironment(X3) has no significant effect on job satisfaction at the sub district office employees, Kerinci district, this is proven by the value (Î²) of 0.066. And based on the test results of the three independent variables tested individually, the most dominant in influencing the job satisfaction of Siulak sub district office employees Kerinci district is the organizational culture (with a coefficient of 0.590). So it can be concluded that in this study (X2) organizational culture is partially a factor that significantly job satisfaction (Y).